How well do doctors understand a scientific article in English when it is not their first language? A randomised controlled trial - Eva Skovlund; Magne Nylenna; Pål Gulbrandsen; Erlend Hem; Martine Rostadmo; Siri Lunde Strømme; Are Brean; Ragnhild Orstavik (BMJ Open)
Introduction English is the lingua franca of science. How well doctors understand English is therefore crucial for their understanding of scientific articles. However, only 5% of the world’s population have English as their first language.Methods Objectives: To compare doctors’ comprehension of a scientific article when read in their first language (Norwegian) versus their second language (English). Our hypothesis was that doctors reading the article in Norwegian would comprehend the content better than those reading it in English.Design: Parallel group randomised controlled trial. We randomised doctors to read the same clinical review article in either Norwegian or English, before completing a questionnaire about the content of the article.Setting: Conference in primary care medicine in Norway, 2018.Participants: 130 native Norwegian-speaking doctors, 71 women and 59 men. One participant withdrew before responding to the questionnaire and was excluded from the analyses.Interventions: Participants were randomly assigned to read a review article in either Norwegian (n=64) or English (n=66). Reading time was limited to 7 min followed by 7 min to answer a questionnaire.Main outcome measures: Total score on questions related to the article content (potential range −9 to 20).Results Doctors who read the article in Norwegian had a mean total score of 10.40 (SD 3.96) compared with 9.08 (SD 3.47) among doctors who read the article in English, giving a mean difference of 1.32 (95% CI 0.03 to 2.62; p=0.046). Age was independently associated with total score, with decreased comprehension with increasing age.Conclusion The difference in comprehension between the group who read in Norwegian and the group who read in English was statistically significant but modest, suggesting that the language gap in academia is possible to overcome.